Heterotrimeric G Protein-Regulated Ca2+ Influx and PIN2 Asymmetric Distribution Are Involved in Arabidopsis thaliana Roots' Avoidance Response to Extracellular ATP - Zhu, Ruojia; Dong, Xiaoxia; Hao, Weiwei; Gao, Wei; Zhang, Wenzhu; Xia, Shuyan; Liu, Ting; Shang, Zhonglin (Frontiers in Plant Science, 2017)
Extracellular ATP (eATP) has been reported to be involved in plant growth as a primary messenger in the apoplast. Here, roots of Arabidopsis thaliana seedlings growing in jointed medium bent upon contact with ATP-containing medium to keep away from eATP, showing a marked avoidance response. Roots responded similarly to ADP and bz-ATP but did not respond to AMP and GTP. The eATP avoidance response was reduced in loss-of-function mutants of heterotrimeric G protein α subunit (Gα) (gpa1-1 and gpa1-2) and enhanced in Gα-over-expression (OE) lines (wGα and cGα). EGTA and Gd3+ remarkably suppressed eATP-induced root bending. ATP-stimulated Ca2+ influx was impaired in Gα null mutants and increased in its OE lines. DR5-GFP and PIN2 were asymmetrically distributed in ATP-stimulated root tips, this effect was strongly suppressed by EGTA and diminished in Gα null mutants. In addition, some eATP-induced genes’ expression was also impaired in Gα null mutants. Based on these results, we propose that heterotrimeric Gα-regulated Ca2+ influx and PIN2 distribution may be key signaling events in eATP sensing and avoidance response in Arabidopsis thaliana roots.